CSF1R inhibition prevents radiation pulmonary fibrosis by depletion of interstitial macrophages. Issue 3 (1st March 2018) - Meziani, Lydia; Mondini, Michele; Petit, Benoît; Boissonnas, Alexandre; Thomas de Montpreville, Vincent; Mercier, Olaf; Vozenin, Marie-Catherine; Deutsch, Eric
Radiation-induced lung fibrosis (RIF) is a delayed side-effect of chest radiotherapy, frequently associated with macrophage infiltration. We aimed to characterise the role of pulmonary macrophages in RIF using human lung biopsies from patients receiving radiotherapy for thorax malignancies and a RIF model developed in C57BL/6 mice after 16-Gy thorax irradiation. High numbers of macrophages (both interstitial and alveolar) were detected in clinical and preclinical RIF. In the preclinical model, upregulation of T-helper (Th)2 cytokines was measured, whereas Th1 cytokines were downregulated in RIF tissue lysate. Bronchoalveolar lavage demonstrated upregulation of both types of cytokines. At steady state, tissue-infiltrating macrophages (IMs) expressed 10-fold more arginase (Arg)-1 than alveolar macrophages (AMs), and a 40-fold upregulation of Arg-1 was found in IMs isolated from RIF. IMs, but not AMs, were able to induce myofibroblast activation in vitro . In addition, whereas depletion of AMs using Clodrosome didn't affect RIF score, depletion of IMs using a clinically available colony-stimulating factor receptor-1 (CSF1R) neutralising antibody was antifibrotic. These findings suggest differential contributions of alveolar versus interstitial macrophages in RIF, highlighting the fibrogenic role of IMs. The CSF1/CSF1R pathway was identified as a new therapeutic target to inhibit RIF. A novel approach to improve the management of radiation-induced lung complications via CSF1R inhibition http://ow.ly/dfWA30h6jxW